Literature Review On English Education In Primary And Secondary Schools In China - Xiaolu, Chen; Hui, Xu (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
This paper identifies different research works published in CNKI during the past decade on English education in primary and secondary schools in China. Here an attempt has been made to summarize the reviews on the above topic. The findings of the study indicates that the study of English education in primary and secondary schools in China is very scanty and lots of scope is there for the further research. The study highlights the problems encountered by English language schools in overseas Chinese townships and also depicts the difficulties faced by them in linking the theoretical background and practice among school children. This paper offers relevant suggestions to overcome the limitations in this field of research. In fine, a comparison was made between English education of primary and secondary schools.